2008
DOI: 10.1080/10683160701340569
|View full text |Cite
|
Sign up to set email alerts
|

Aggression Control Therapy for violent forensic psychiatric patients: First results

Abstract: Aggression Control Therapy (ACT), a treatment programme developed in the Netherlands for violent forensic psychiatric patients with a conduct disorder or antisocial personality disorder, was investigated in two studies. In the first study, the personality traits and problem behaviours of these patients and a normative Dutch population were compared, and then the traits and behaviours of patients who completed the ACT were compared with those who dropped out. In the second study, the ACT was evaluated by compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Participants reported to have better capacity to control their impulses at the end of program as well. Previous research has shown that cognitive behavioral therapy (CBT) was effective in reducing anger and aggression in various populations, such as incarcerated offenders (Blacker et al, 2008), forensic outpatients (Hornsveld et al, 2008), and individuals with mental illnesses or mild mental disabilities (Reiss, Quayle, Brett, & Meux, 1998;Taylor, Novaco, Gillmer, Robertson, & Thorne, 2005). Our research extends these findings by demonstrating that CBT can be effective in reducing anger and aggression for youth offenders as well.…”
Section: Treatment Changesupporting
confidence: 70%
See 1 more Smart Citation
“…Participants reported to have better capacity to control their impulses at the end of program as well. Previous research has shown that cognitive behavioral therapy (CBT) was effective in reducing anger and aggression in various populations, such as incarcerated offenders (Blacker et al, 2008), forensic outpatients (Hornsveld et al, 2008), and individuals with mental illnesses or mild mental disabilities (Reiss, Quayle, Brett, & Meux, 1998;Taylor, Novaco, Gillmer, Robertson, & Thorne, 2005). Our research extends these findings by demonstrating that CBT can be effective in reducing anger and aggression for youth offenders as well.…”
Section: Treatment Changesupporting
confidence: 70%
“…Criminogenic needs that have been identified as being relevant to youth aggression include: (i) anger (Bryan & Day, 2006;Howells, 2004), (ii) impulsivity (Henry, Caspi, Moffitt, & Silva, 1996;Piquero, MacDonald, Dobrin, Daigle, & Cullen, 2005), and (iii) empathy deficits (Jolliffe & Farrington, 2004;Lauterbach & Hosser, 2007). Empirical findings suggest a promising effect of interventions on reducing the aggression and anger of violent offenders (Blacker, Watson, & Beech, 2008;Davidson et al, 2009;Hornsveld, Nijman, & Kraaimaat, 2008). However, less is known about the effects of treatments on self-control and empathy (Day, Casey, & Gerace, 2010;Mann & Barnett, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hornsveld and Nijman (2005) reported a dropout rate of 36% from a cognitive behavioural treatment programme for psychotic forensic patients. In antisocial violent patients Hornsveld et al. (2008a) found a lower drop‐out rate of 13% withdrawal rate of forensic inpatients from an Aggression Control Therapy (which was derived from Aggression Replacement Therapy).…”
Section: Discussionmentioning
confidence: 99%
“…A standard set of questionnaires was submitted individually to the patients prior to a cognitive-behavioural group therapy (Hornsveld et al, 2008). In this study the scores on these questionnaires were used to determine the concurrent and discriminant validity of the BVAQ.…”
Section: Methodsmentioning
confidence: 99%